2017
DOI: 10.1111/ijd.13759
|View full text |Cite
|
Sign up to set email alerts
|

Study of efficacy and safety of noncultured, extracted follicular outer root sheath cell suspension transplantation in the management of stable vitiligo

Abstract: NC-EHF-ORS-CS is a useful minimally invasive therapy for vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Assessing these markers by flow cytometry, we found that the mean percentage of both mesenchymal and keratinocyte stem cells were greater (although not significantly so) in group A (Table ). In other studies that used trypsin alone, CD200 positivity was in the range of 8.4% and 7.91%, which was comparable to this study . We performed immunohistochemistry to assess the number of melanocytes, and found that the fraction of HMB45+ cells was also greater in group A ( P = 0.12).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Assessing these markers by flow cytometry, we found that the mean percentage of both mesenchymal and keratinocyte stem cells were greater (although not significantly so) in group A (Table ). In other studies that used trypsin alone, CD200 positivity was in the range of 8.4% and 7.91%, which was comparable to this study . We performed immunohistochemistry to assess the number of melanocytes, and found that the fraction of HMB45+ cells was also greater in group A ( P = 0.12).…”
Section: Discussionsupporting
confidence: 87%
“…Studies employing conventional NC-EHF-ORS-CS have achieved mean repigmentation rates of 65.7%, 52% and even 80.15% at 6 months. 2,22,23 The overall repigmentation in this study was comparatively less, which may be due to patient selection factors or run-off of the liquid-based low-viscosity suspension from the recipient site. The latter problem could be overcome by using hyaluronic acid or hydroxypropyl-methylcellulose to increase the suspension viscosity.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…No difference in improvement according to the type of vitiligo was noted in a recent study using outer root sheath hair follicle suspension (ORSHFS) in the treatment of 25 cases of stable vitiligo (nine SV, eleven acrofacial vitiligo, five GV). 44 …”
Section: Introductionmentioning
confidence: 99%
“…As a result, these cells can escape from the immune suppression of T lymphocytes. Under certain condition, they can be stimulated to activate and differentiate into functional melanocytes and migrate into the epidermis to replace the damaged melanocytes, then forming the repigmenting spots (Kumar et al, ; Schneider, Dieckmann, Rabe, Simon, & Savkovic, ). The occurrence of vitiligo may also be related to the enhancement of local or systemic oxidative stress in vivo (Shi et al, ).…”
Section: Discussionmentioning
confidence: 99%